2016
DOI: 10.1038/srep39388
|View full text |Cite
|
Sign up to set email alerts
|

Tuning apparent friction coefficient by controlled patterning bulk metallic glasses surfaces

Abstract: Micro-honeycomb structures with various pitches between adjacent cells were hot-embossed on Zr35Ti30Cu8.25Be26.75 bulk metallic glass surface. The effect of pitch geometry on the frictional behavior of metallic glass surface was systematically investigated. The results revealed that all textured metallic glass surfaces show a reduction in friction coefficient compared to smooth surface. More intriguingly, the friction coefficient first decreased and then increased gradually with increasing pitches. Such unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The interest of this study lies not only in the numerical modeling of friction in itself, but also has practical purposes: there are many studies relative to bio-inspired materials [20]- [23] or biological materials [24]- [28] that reproduce non-trivial geometries that can not be reduced to one-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest of this study lies not only in the numerical modeling of friction in itself, but also has practical purposes: there are many studies relative to bio-inspired materials [20]- [23] or biological materials [24]- [28] that reproduce non-trivial geometries that can not be reduced to one-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%
“…a Young's modulus E = 10 MPa, which it typical for a soft polymer or rubber-like material and a density ρ = 1.2 g/cm 3 . The distance between blocks l in the model is an arbitrary parameters representing the smallest surface feature that can be taken into account and it is chosen by default as l = 10 −3 cm, so that the order of magnitude matches those typical of surface structures used in experiments [20]- [23].…”
Section: Introductionmentioning
confidence: 99%
“…First, the surface can be polished in a spatially variable manner or using different processes in order to have a varying roughness and thus varying local friction coefficients. Secondly, a surface with a gradient in the frictional properties can be obtained by appropriately fabricating and arranging microscopic structures of variable geometries or sizes, giving rise to variable local friction coefficients [ 40 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The combined properties of both superhydrophobicity and strong adhesion toward liquid exhibit promising applications as dry adhesives and transport of liquid micro-droplets, as well as desirable mechanical and corrosion resistance showing potential applications in modern industries [64]. Furthermore, Li et al revealed that MGs surfaces with hot-embossed textures exhibit low friction coefficient especially under dry contact (see Figure 8), which indicates that the lifetime of the textured surfaces could be optimized by minimizing friction [65]. Thermoplastic Forming of Metallic Glasses http://dx.doi.org/10.5772/intechopen.78016…”
Section: Potential Applicationsmentioning
confidence: 99%